Synthesis of cerium-doped yttrium aluminum garnet nanopowder low-temperature reaction combustion method - Do, Ngoc Chung (H. : ĐHQGHN, 2017)
Nanopowders of cerium doped yttrium aluminum garnet (Y3Al5O12:Ce3+) - YAG:Ce were prepared by low-temperature sol-gel method. High-purity Y2O3, Al(NO3)3.9H2O, Ce(NO3)3·6H2O in the presence of citric acid as complexing agent were used as initial materials. The YAG:Ce nanopowders were characterized using X-ray diffraction, SEM, dynamic light scattering particle size analyzer and a high resolution spectrometer-Microspec-235b. The particle sizes of the YAG:Ce powder were estimated from SEM image and dynamic light scattering particle size analyzer to be 4 – 80 nm. The annealing effect on the crystalline structure of the samples was reported.